Zmiana wartości aktywów długoterminowych, przyczyny, rozwiązania, zgodność z międzynarodowymi standardami rachunkowości i ich wpływ na łotewskie prawo podatkowe - Medne, Anna; Zarina, Vita (Changes of Long-Term Assets Value, Causes, Decisions, Coordination with International Standards of Accounting and their Impact on Tax Legislation of Latvia, 2005)
Every enterprise, taking as a basis the laws and common principles of accounting, has the right to elaborate its own accounting policy. It also concerns the accounting of enterprise's assets. The law "On Annual Reports of Enterprises" defines that long-term investments are to be evaluated according to their original value, i.e. the cost of their acquisition or production. During economic activities, the value of long-term assets may change, causing the necessity of their revaluation according to the changes of the market prices. Revaluation of long-term investments is connected with enterprise income tax and immovable property tax.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 46-53